2015
DOI: 10.1177/1082013215592732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high pressure processing on color, bioactive compounds, polyphenol oxidase activity, and microbiological attributes of pumpkin purée

Abstract: Physicochemical parameters, bioactive compounds' content (carotenoids and total phenols), total antioxidant activity, and enzymatic activity of polyphenol oxidase (PPO) were evaluated after high pressure processing (HPP) on a pumpkin purée (cv. 'Butternut'). Three pressure levels (400, 500, and 600 MPa) were combined with three holding times (200, 400, and 600 s). The applied treatments reduced the levels of total aerobic mesophilic (TAM), total psychrophilic and psychrotrophic bacteria (TPP), and molds and ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Total color difference was significantly higher in treated pomegranate juice sample at 350, 450 and 550 MPa compared to a control untreated sample, and a decrease was observed during storage (Varela-Santos et al., 2012). Additionally, a study conducted with pumpkin puree treated with HHP found that color was better preserved (total color difference lower than 2) when using lower pressure levels (400 MPa rather than 600 MPa) and treatment time (200 s rather than 600 s) (González-Cebrino et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Total color difference was significantly higher in treated pomegranate juice sample at 350, 450 and 550 MPa compared to a control untreated sample, and a decrease was observed during storage (Varela-Santos et al., 2012). Additionally, a study conducted with pumpkin puree treated with HHP found that color was better preserved (total color difference lower than 2) when using lower pressure levels (400 MPa rather than 600 MPa) and treatment time (200 s rather than 600 s) (González-Cebrino et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…High pressure processing (HPP) is a promising alternative to traditional thermal processing due to its competent inactivation of microorganisms (González-Cebrino et al., 2016) and minimal damage to food nutritional and sensory qualities (Guerrero-Beltrán et al., 2005; Oey et al., 2008). Evidence of HPP effects on fruits and vegetables has verified that HPP had potential on desirable textural characteristics preservation (De Roeck et al., 2010; Vervoort et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although oxidative enzyme activity was not evaluated, we can hypothesize that HHP processing did not inactivate polyphenol oxidase, as reported by Brannan et al [31] and González-Cebrino et al [32] in papaya pulp and pumpkin purée, respectively. Jesus et al [32] observed that inactivation of polyphenol oxidase only occurred when açaí pulp was HHP-processed at 65 • C. In that sense, HHP processing at temperatures higher than room temperature deserves to be investigated for jussara juice aiming at preserving anthocyanins. Anthocyanins content in jussara juices decreased drastically (98%, on average) in the first 15 days during refrigerated storage (Figure 5, p < 0.0001), indicating that HHP processing was ineffective (p = 0.88) in preventing the degradation of anthocyanins.…”
Section: Hhp Processing On Retention Of Anthocyanins Content and Antioxidant Activity Of Jussara Juice During Refrigerated Storage For 60mentioning
confidence: 79%